DEVIANT BEHAVIOR PROBLEMS IN ADOLESCENTS SOCIO-PSYCHOLOGICAL ASPECTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article proposes the socio-psychological aspects of adolescents, and also consider the problems of deviant behavior.